2023
DOI: 10.1186/s12920-023-01510-1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of autism in a rare case of tyrosine hydroxylase deficiency: a case report

Abstract: Background Tyrosine hydroxylase deficiency (THD) is a rare movement disorder with broad phenotypic expression caused by bi-allelic mutations in the TH gene, which encode for tyrosine hydroxylase (TH) protein. Some patients with THD have improvement in dystonia with carbidopa–levodopa, a synthetic form of dopamine typically used in Parkinson’s disease, and are considered to have dopa-responsive THD. THD has been found in 0.5–1 per million persons, although due to overlapping symptoms with other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…We compiled the summary from Dong et al, encompassing all TH deficiency cases reported through 2018 (Dong et al, 2020) and all Segawa patients published thereafter until 2023 (Atanasoska et al, 2023;Bijarnia-Mahay et al, 2020;Champagne et al, 2022;Chen et al, 2020;Couto et al, 2019;Hou et al, 2019;Hull et al, 2021;Janssen et al, 2021;Kuseyri Hubschmann et al, 2021;Panda et al, 2022;Reyes et al, 2023;Wang et al, 2022). In total, we summarized the clinical phenotypes of all 175 reported Segawa cases.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…We compiled the summary from Dong et al, encompassing all TH deficiency cases reported through 2018 (Dong et al, 2020) and all Segawa patients published thereafter until 2023 (Atanasoska et al, 2023;Bijarnia-Mahay et al, 2020;Champagne et al, 2022;Chen et al, 2020;Couto et al, 2019;Hou et al, 2019;Hull et al, 2021;Janssen et al, 2021;Kuseyri Hubschmann et al, 2021;Panda et al, 2022;Reyes et al, 2023;Wang et al, 2022). In total, we summarized the clinical phenotypes of all 175 reported Segawa cases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Until now, more than 100 cases of Segawa syndrome have been reported globally (Reyes et al, 2023). However, due to the rarity and high heterogeneity of Segawa syndrome, the spectrum of pathological mutations in the TH gene, associated clinical symptoms, and the correlation between genotype and phenotype, as well as genotype and treatment outcomes with dopamine, are not fully understood (Chen et al, 2020;Dong et al, 2020;Reyes et al, 2023). Further studies are required to enhance our comprehension of this disease.…”
Section: Introductionmentioning
confidence: 99%